Invention, copyright, and digital writing - Rife, Martine Courant (Southern Illinois University Press, 2013)
This is an empirical, mixed-methods study of copyright issues that speaks to writing specialists and legal scholars about the complicated intersections of rhetoric, technology, copyright law, and writing for the Internet. The author opens up new conversations about how invention and copyright work together in the composing process for digital writers and how this relationship is central to contemporary issues in composition pedagogy and curriculum. In this era of digital writing and publishing, composition and legal scholars have identified various problems with writers' processes and the law's construction of textual ownership, such as issues of appropriation, infringement, and fair use within academic and online contexts. This book unpacks digital writers' complex perceptions of copyright, revealing how it influences what they choose to write and how it complicates their work. -- Provided by publisher.